FACTORS AFFECTING BANKING PROFIT ABILITY IN INDONESIA (STUDIES AT BANK BRI, BANK BNI, AND BANK BTN) - Budiyono Budiyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2017)
The aim of this research is to know the influence of inflation, BI Rate and Non Performing Loan (NPL) toward the profitability of BUMN bank studies in Bank Rakyat Indonesia, Bank Negara Indonesia, and Bank Tabungan Negara. Profitability is the company's ability to make a profit. The purpose of a company's profitability analysis is to measure the level of business efficiency achieved by the company concerned. The population in this research is all quarterly financial report of Commercial Banks. While the sample used is the financial statements of the first quarter of 2013 until the fourth quarter of 2016 in Bank Rakyat, Bank Negara Indonesia, and Bank Tabungan Negara. This research used multiple linear regression analysis. The result of this research using F test shows that simultaneously the independent variable of inflation, BI Rate, and NPL have significant effect on profitability. Partially the result using t test obtained that BI Rate and Non Performing Loan (NPL) have significant effect on profitability while inflation has no effect on profitability. Key words: Inflation, BI Rate, NPL, Profitability.